Semblantes de la publicidad posmoderna - Centocchi, Claudio Fabián (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2010)
This paper describes some of the strategies characterizing “postmodern” advertising. For this purpose, I will elaborate on some observations made in my previous article published in the first issue of Pensar la Publicidad. The focus will be mainly on a series of thematic, narrative and argumentative features which are typical of postmodern advertising style and allow the manifestation of an influencer/enunciator who is closer to the addressee than the traditional enunciator and intends to meet his/her goals (which in fact are the same as in every advertising text) in a more indirect and paradoxical way, taking advantage of the current consumer’s profile. This kind of advertising presents itself as innovating and critical as compared to the predominant style, but the real objective is for everything to stay as it is so that the pragmatic efficiency should not decline.
Keywords: Postmodern advertising; Lack; Comical; Spectacular; Proximity